INFLUENCER MARKETING FACTORS AFFECTING CONSUMER BEHAVIOR - Tereza Šulanová; Marta Žambochová; Michaela Jánská (Trendy v podnikání, 2025)
Influencer marketing is a current phenomenon and a crucial part of digital marketing strategies for companies, particularly targeting Generation Y and Z, who are highly active on social media. The aim of this study is to identify the key factors influencing consumer decisions to follow influencers and to make purchases based on their recommendations, which is essential for optimizing marketing campaigns and better targeting potential customers. Through an online survey, we collected data from 337 respondents, which we then analyzed using descriptive statistics and non-parametric tests. The results show that the strongest factor influencing the following of influencers is the type of content they create (inspirational, entertaining, educational), followed by the influencer’s thoughts and opinions, and shared interests with their audience. Influencer credibility also significantly attracts users. In contrast, the number of followers and the influencer's background have minimal impact on consumer decision-making. For purchasing a promoted product, it is essential whether the influencer genuinely uses the product in their everyday life. The study concludes with recommendations for companies to focus on authenticity and the real usage of products by influencers in their campaigns, as this has proven to be more important than their popularity.